An update on diagnosis and treatment of female pattern hair loss. (August 2013) - Mubki, Thamer; Shamsaldeen, Omar; McElwee, Kevin J; Shapiro, Jerry
Female pattern hair loss (FPHL) is the most common cause of hair loss in women. It has a greater psychosocial morbidity than that of male pattern hair loss. The clinical presentation of FPHL is distinctive with hair thinning usually confined to the crown region of the scalp. The frontal hair line is usually spared; however, it can be affected in some patients. Miniaturization of terminal scalp hair and shortening of the anagen growth phase of the hair cycle results in growth of thinner and shorter hair fibers. Diagnosis is usually made clinically. Recent advances in digital image analysis has increased the use of dermatoscopy in the diagnosis of FPHL and as a consequence, reduced the need for doing skin biopsies. Many medical and surgical treatments are currently available with various success rates. In this review article, we discuss the major recent advances in the diagnosis and management of FPHL.